Single Subject Research: Implementasi Pembelajaran Usaha dan Energi dengan Metode Berbasis Masalah Pada Siswa Introvert - Muhammad Khoerul Musafi; Neng Nenden Mulyaningsih; Maria Dewati (Schrodinger Jurnal Ilmiah Mahasiswa Pendidikan Fisika, 2022)
Critical thinking skills are needed to be able to follow physics learning. Because the concept of physics has a mathematical language. The mathematical ability of introverted students can be improved by using contextual problems. Therefore, mathematical learning requires a more Student Centered method in the sense that the Physics learning process which still uses conventional methods is replaced with PBL to train students to increase their curiosity about complex things. This study aims to improve critical thinking skills in introverted students and the effectiveness of problem-based learning methods to improve critical thinking skills in introverted students. The research method is carried out using the A-B design on the Single Subject Research method (single subject design). Data analysis techniques using visual analysis or descriptive statistics. Based on the results of the study, it shows that there is a trend of increasing critical thinking skills of introverted students in two conditions as evidenced by the analysis of data under conditions and data analysis between conditions.